FIDIC yellow book : a companion to the 2017 plant & design build contract - Srensen, Jakob B. (ICE Publishing, 2019)
FIDIC Yellow Book is a guide for anyone involved in preparing, administering, or contributing to the FIDIC suite of contracts, 2017 edition. Designed as a companion for both the first-time and also more experienced user, the book presents an accessible guide to the 21 clauses of the 2017 FIDIC Conditions of Contract, using the Conditions of Contract for Plant & Design Build (Yellow Book) as a basis. Opening chapters provide an introduction to international construction contracts, including the entire FIDIC suite of contracts, and there is also a list of definitions of key terms. Chapters in Part 2 provide a brief introduction to each of the Clauses and Sub-Clauses in the Yellow Book, and explain how they are interlinked. A final section provides a concise practical guide to the use of the FIDIC Conditions, and a summary of special provisions discussed in Part 2.
Keywords: International Federation of Consulting Engineers. -- Plant and design-build contract 2017.; Construction contracts -- Handbooks, manuals, etc.; elektronické knihy; electronic books